Increased oxidative stress in preschool children exposed to passive smoking - KOÇYİĞİT, ABDÜRRAHİM; YILDIRIM, Faruk; Sermetow, Kabil; Aycicek, Ali; Kocyigit, ABDÜRRAHİM; Erel, Ozcan (My University, 2011)
Objectives: To study the effect of passive cigarette smoking on plasma oxidative and antioxidative status in passive smoking preschool children and to compare them with controls.